Possibility-Driven Design and Responsible Use of AI for Sustainability - Salo-Lahti, Marika; Haapio, Helena (Ledizioni, 2024)
Much of the legal scholarship has focused on past or present problems and issues rather than future possibilities. Practitioners involved in legal drafting have focused primarily on conflicts and legal enforcement, rather than on goals and successful implementation. For scholars and practitioners with a proactive legal and design mindset, goals and possibilities drive the work. In addition to mindset and think-ing, doing – implementation – is critical. In this paper, we merge proactive legal thinking with possibility-driven design and move from thinking to doing, using templates, design patterns and AI tools. Our examples illustrate how the responsible use of AI tools can help navigate the new legal landscape of sustainability, and how possibility-driven legal design can be used as a framework for balancing the needs and expectations of people, businesses and society at large. By working in this way, we argue, it is possible to achieve better investment decisions and more sustainable and responsible contracting – ultimately better business and a better society.
Keywords: fi=Talousoikeus|en=Business Law|